Biosynthesis of surface-active compounds by Bacillus genus bacteria - Іванисько, О. В. (Problems of Environmental Biotechnology, 2013)
Biosurfactants – surface-active agents (surfactants) of bacterial origin with pronounced multifunctional properties. In this article presents the data in the literature about the ability of representatives of the genus Bacillus to the formation of surfactants and practical use in industry, biology and medicine. The characteristics of lipopeptide synthesized by representatives of the genus Bacillus.